A Study on the Implementation of Capital Punishment within Indonesia's Criminal Justice System through the Lens of Human Rights - Hidayah, Ahdiyatul (Universitas Al Azhar Indonesia, 2025)
The death penalty remains a contentious issue, sparking debate both nationally and internationally. It represents the harshest form of punishment within the criminal justice system. This sanction is deemed necessary by some due to its strong deterrent effect on individuals committing grave offenses. This research aims to examine how the death penalty is implemented within Indonesia's legal framework. The study employs a normative juridical method, relying on primary sources such as legal texts, academic literature, and relevant regulations. The analysis is conducted descriptively. Currently, the death penalty is no longer regarded as the primary form of punishment but rather as a special and alternative measure. The findings indicate that judges consider multiple considerations when deciding on capital punishment, including legal principles, existing laws, regulatory frameworks, and religious factors. The death penalty is applicable for the most severe crimes as stipulated by law. Indonesian law treats foreign nationals and citizens equally in this regard. In judicial decisions, judges evaluate both juridical evidence—such as testimonies from witnesses and experts, defendant statements, and other proofs—and non-legal factors that may either mitigate or intensify the defendant’s sentence. Keyword: Death Penalty, Human Rights, Sanctions